2012
DOI: 10.1089/g4h.2011.0005
|View full text |Cite
|
Sign up to set email alerts
|

Pilot Study of an Active Screen Time Game Correlates with Improved Physical Fitness in Minority Elementary School Youth

Abstract: Objective: The aim of our feasibility study was to examine the acceptability and utility of ''Dance Dance Revolution'' (DDR) (Konami of America, Redwood City, CA)) to increase physical fitness in 8-11-year-old black and Hispanic youth. Subjects and Methods: Twenty-eight 4 th and 5 th grade children attending an afterschool program participated. Outcomes included physical activity, physical fitness, use of home DDR, survey of safety and acceptability, anthropometrics, and fasting metabolic profile measured at b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
41
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(44 citation statements)
references
References 63 publications
(57 reference statements)
3
41
0
Order By: Relevance
“…75 In the other study, participants had access to a dance game at home and also in an afterschool program. 81 This study also provided each participant two dance mats at home and reported improved physical fitness and increased AVG play. 81 None of these strategies has been used sufficiently to reach a firm conclusion regarding the effects.…”
Section: Studies On the Choices Between Avgs And Sedentary Al-mentioning
confidence: 99%
See 3 more Smart Citations
“…75 In the other study, participants had access to a dance game at home and also in an afterschool program. 81 This study also provided each participant two dance mats at home and reported improved physical fitness and increased AVG play. 81 None of these strategies has been used sufficiently to reach a firm conclusion regarding the effects.…”
Section: Studies On the Choices Between Avgs And Sedentary Al-mentioning
confidence: 99%
“…Effects of AVGs on habitual PA or change of PA A cross-sectional survey indicated a positive association between AVG play and PA. 88 Among the 21 intervention studies, [73][74][75][76][77][78][79][80][81][82][83][84][85][86][87][89][90][91][92][93][94] 13 were RCTs, and 4 RCTs 73-75,87 indicated they were pilot studies ( Table 4).…”
Section: Studies On the Choices Between Avgs And Sedentary Al-mentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have shown that active videogames can have beneficial effects on physical activity and related health outcomes. [10][11][12][13] On the other hand, several other studies have failed to find significant effects. 14,15 So how effective are active videogames?…”
mentioning
confidence: 98%